SOSIALISASI PEMBERDAYAAN MASYARAKAT BERBASIS DIGITAL DALAM MENGGALI POTENSI DESA MENUJU DESA MANDIRI, UNGGUL DAN PRODUKTIF DI KELURAHAN JELITIK, SUNGAILIAT, BANGKA - Dalimunthe, Desy Yuliana; Kustiawan, Elyas; Ulum, Miftahul; Simarmata, Andreas Cornel (Jurnal Abdi Insani, 2024)
Jelitik Village is one of the Villages located in Sungailiat District, Bangka Regency, Bangka Belitung Islands Province which has considerable tourism potential. This tourism potential can be used to improve the local economy of the community. The development of this tourism potential is also in line with the direction of the Bangka Regency government in the establishment of a Special Economic Zone (KEK) which includes Jelitik Village. This potential should be presented digitally so that it can be accessed by all citizens. This service activity aims to explore the type of potential of the village/sub-district so as to encourage the independence of the community in the village through digital-based community empowerment. Socialization techniques to the community are an option in realizing this service activity by involving all village officials and PKK management in Jelitik Village. In addition, identification and analysis of partner needs are also needed before the implementation of this service activity. The results obtained based on the results of the analysis were that participants tended to give very agreeable and agreed answers about the benefits of the activity, the suitability of the theme, the clarity of the material and the adequacy of the infrastructure used during this service activity and there was one participant who answered disagreeing about the clarity of the material. In addition, from the results of the questionnaire analysis, it can be seen that the highest percentage is at 89%, namely respondents who answered yes to question 1. With the implementation of this socialization, the people of Jelitik are beginning to realize the importance of using digital technology in managing tourism potential. Based on the results of the analysis, with the implementation of this socialization, the people of Jelitik are beginning to realize the importance of using digital technology in managing tourism potential.